2021
DOI: 10.3390/ijms221910895
|View full text |Cite
|
Sign up to set email alerts
|

Structural Alterations of Antigens at the Material Interface: An Early Decision Toolbox Facilitating Safe-by-Design Nanovaccine Development

Abstract: Nanomaterials have found extensive interest in the development of novel vaccines, as adjuvants and/or carriers in vaccination platforms. Conjugation of protein antigens at the particle surface by non-covalent adsorption is the most widely used approach in licensed particulate vaccines. Hence, it is essential to understand proteins’ structural integrity at the material interface in order to develop safe-by-design nanovaccines. In this study, we utilized two model proteins, the wild-type allergen Bet v 1 and its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 55 publications
(60 reference statements)
0
12
0
Order By: Relevance
“…As the initial step, the SiNPs and functionalized SiNPs were characterized for their primary size and morphology. The TEM images of the particles displayed a uniform spherical shape with a primary size of 51.02 ± 3.80 nm (SiNP), 47.31 ± 4.72 nm (SiNP_A) and 50.42 ± 4.57 nm (SiNP_M) ( Figure 1 ) [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As the initial step, the SiNPs and functionalized SiNPs were characterized for their primary size and morphology. The TEM images of the particles displayed a uniform spherical shape with a primary size of 51.02 ± 3.80 nm (SiNP), 47.31 ± 4.72 nm (SiNP_A) and 50.42 ± 4.57 nm (SiNP_M) ( Figure 1 ) [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…Allergens are known to form a stable corona on the particle interface [ 43 ]. We have previously demonstrated that silica nanoparticles both mesoporous and nonporous adsorb Bet v 1, effectively forming a biocorona [ 22 , 44 ]. The efficiency of binding was determined by SDS-PAGE and BCA assay.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Protein adsorption onto the NM surface can favor conformational changes in the protein, thereby imposing destabilization of the native protein fold, reducing their thermal and pH stability and eventually leading to protein denaturation. Allergens adsorbed onto the surface of amorphous silica NPs have been reported to induce changes in the fold stability, especially in the alpha‐helical structures of Bet v 1 (the major birch pollen allergen), thereby altering the immunological response (L. Johnson et al, 2021 ), while the formation of the tubulin protein corona on the surface of titanium dioxide (TiO 2 ) NPs imposed an inhibitory effect on tubulin polymerization, an important step in cell division. The interaction with NPs altered the folding of both tubulin and microtubule proteins eliciting functional alterations (Gheshlaghi et al, 2008 ).…”
Section: Protein Corona Formation As a Genuine Nanomaterial‐specific Miementioning
confidence: 99%
“…In general, when allergenic proteins bind to nanoparticles, this can induce structural alterations. 21,22 In addition, they may bind in a non-randomized manner and, thus, selectively hide or expose allergenic epitopes on their surface. 23,24 Consequently, their biological effects may change, increasing or decreasing the immune response towards them.…”
Section: Introductionmentioning
confidence: 99%